Book Review: Viking and Iron Age expanded Boats by Ole Crumlin-Pedersen and Hanus Jensen - Robert Holtzman (EXARC Journal)
Viking and Iron Age expanded boats is the English version of the simultaneously-published Danish edition, Udspændte både fra vikingetid og jernalder. The two editions are identical in layout and are heavily illustrated with colour and black and white photographs, and line drawings from a variety of sources. This review is of the English edition. By “expanded boats”, the authors mean those craft that are more often termed “expanded logboats” (i.e., dugout canoes with their hulls stretched sideways for greater beam), regardless of whether or not they are also “extended” by the addition of strakes (longitudinal planking that runs from bow to stern) to the logboat base.